Accompanied versus unaccompanied walking for continuous oxygen saturation measurement during 6-min walk test in COPD: a randomised crossover study. Issue 3 (2nd August 2021) - Riegler, Thomas F.; Frei, Anja; Haile, Sarah R.; Radtke, Thomas
The aim of this study was to determine if there is a difference in 6-min walk test (6MWT) distance when the assessor accompanies the patient to continuously measure peripheral oxygen saturation ( S pO2 ) compared to the patient walking unaccompanied.  We conducted a randomised crossover study to evaluate the impact of the assessor walking with the patient during the 6MWT (6MWTwith ) versus the patient walking alone (6MWTwithout ). At the end of a pulmonary rehabilitation programme, each patient performed two 6MWTs in random order and separated by a 30-min rest.  49 patients with chronic obstructive pulmonary disease (COPD) (Global Initiative for Obstructive Lung Disease classification II–IV) were included. In a regression model adjusting for period and subject, accompanying the patient resulted in a lower walking distance (mean difference −9.1 m, 95% CI −13.9– −4.3, p=0.0004). Notably, six patients walked more than 30 m farther (minimal important difference) in one of the two conditions (6MWTwith : n=1, 6MWTwithout : n=5). There were no between-sequence-group differences in heart rate, dyspnoea, leg fatigue and S pO2 . The median (interquartile range) number and duration of S pO2 signal artefacts were high but not different between the experimental conditions (6MWTwith : 17 (4–24), 34 s (7–113 s); 6 MWTwithout : 11 (3–26), 24 s (4–62 s)).  At a study population level, we observed a statistically significant difference in 6MWT distance between the two experimental conditions; however, the magnitude of difference was small and may not be clinically relevant. Nevertheless, in a clinical setting, unaccompanied walking resulted in a substantially higher walking distance in individual patients, pointing towards strictly standardised testing methodology, in particular in pre–post study designs. Accompanied walking during a 6MWT versus unaccompanied walking results in shorter walked distance (mean difference −9.1 m, 95% CI −13.9– −4.3 m). No differences in nadir S pO2 or oximetry artefacts were noted between accompanied and unaccompanied walking. https://bit.ly/3tBjfCq